Lines, triangles, and nets: A framework for designing input technologies and interaction techniques for computer-aided design. (December 2019) - Erdolu, Emek
This article serves to the larger quest for increasing our capacities as designers, researchers, and scholars in understanding and developing human-computer interaction in computer-aided design. The central question is on how to ground the related research work in input technologies and interaction techniques for computer-aided design applications, which primarily focus on technology and implementation, within the actual territories of computer-aided design processes. To discuss that, the article first reviews a collection of research studies and projects that present input technologies and interaction techniques developed as alternative or complimentary to the mouse as used in computer-aided design applications. Based on the mode of interaction, these studies and projects are traced in four categories: hand-mediated systems that involve gesture- and touch-based techniques, multimodal systems that combine various ways of interaction including speech-based techniques, experimental systems such as brain-computer interaction and emotive-based techniques, and explorations in virtual reality- and augmented reality-based systems. The article then critically examines the limitations of these alternative systems related to the ways they have been envisioned, designed, and situated in studies as well as of the two existing research bases in human-computer interaction in which these studies could potentially be grounded and improved. The substance of examination is what is conceptualized as "frameworks of thought"—on variables and interrelations as elements of consideration within these efforts. Building upon the existing frameworks of thought, the final part discusses an alternative as a vehicle for incorporating layers of the material cultures of computer-aided design in designing, analyzing, and evaluating computer-aided design-geared input technologies and interaction techniques. The alternative framework offers the potential to help generate richer questions, considerations, and avenues of investigation.